2016
DOI: 10.1590/1678-4766e2016005
|View full text |Cite
|
Sign up to set email alerts
|

Mammal inventories in Seasonal Neotropical Forests: traditional approaches still compensate drawbacks of modern technologies

Abstract: ABSTRACT. Variation in body size, behavior, feeding habits and habitat use patterns in medium-and large-sized mammals infl uence the adequacy of sampling methods to register presence and abundance. Moreover, even if methods are similarly adequate, diff erent methodologies result in distinct costeffi ciency relationships (i.e. some may have reduced costs, be less time-consuming and/or require less-skilled technicians). Focusing on three diff erent sampling methods commonly used to monitor medium and large mamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…The combination of different sampling methods (e.g., camera trap, census, and trail search) proved to be efficient at recording considerable species richness in a short sampling period, which reinforces the importance of combining different methodologies to increase sampling success. According to Carvalho et al (2016), the most efficient methods to sample medium-and large-sized mammals involved searching for indirect (footprints, feces, and burrows) and direct (observation) records. Both in our study and in Carvalho et al (2016), camera traps recorded approximately half of the species found by other methods, indicating the need for methodological variability for survey studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The combination of different sampling methods (e.g., camera trap, census, and trail search) proved to be efficient at recording considerable species richness in a short sampling period, which reinforces the importance of combining different methodologies to increase sampling success. According to Carvalho et al (2016), the most efficient methods to sample medium-and large-sized mammals involved searching for indirect (footprints, feces, and burrows) and direct (observation) records. Both in our study and in Carvalho et al (2016), camera traps recorded approximately half of the species found by other methods, indicating the need for methodological variability for survey studies.…”
Section: Discussionmentioning
confidence: 99%
“…According to Carvalho et al (2016), the most efficient methods to sample medium-and large-sized mammals involved searching for indirect (footprints, feces, and burrows) and direct (observation) records. Both in our study and in Carvalho et al (2016), camera traps recorded approximately half of the species found by other methods, indicating the need for methodological variability for survey studies. Still, the use of camera traps is an important methodology for recording cryptic and less abundant species, which are rarely detected by other methods (Melo et al 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Positioning camera traps along such trails may increase capture success rates. The short-term effectiveness of camera traps may be questionable for detection of species (Carvalho, Rosalino, & Esbérard, 2016), because not all species that occur in a given area will be photo-captured quickly. The capture success rate of 0.187 photos/trap-day could be considered ineffective for a short period, but over many years of study it was sufficient to enable identification of 21 of the 30 species of medium and large mammals that occur in the Araucaria High Plains (Marques, Cademartori, & Pacheco, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The transects were walked by two pairs of researchers, who were able to walk all the ten transects within a day. Each transect was surveyed for 40 days (see Carvalho et al, 2016 for a complete description of the methods).…”
Section: Atlantic Forest Mammalsmentioning
confidence: 99%